Impacts of the recession and horse slaughter ban on the U.S. thoroughbred industry - Garrett, Brandon (Kansas State University, 2013)
Over the last decade, the United States horse industry has seen a decline in all segments of the industry. Both people and organizations within and outside the industry have debated the cause of this decline, with the 2007 horse slaughter ban being at the center of this debate. The purpose of the report is to analyze a specific segment of the industry to determine what has led to this decline over the last decade. To do this, we will look specifically at the total number of thoroughbreds sold over a thirty-year history, and using regression analysis, determine if a controversial bill that banned the slaughter of horses in the United States for the purpose of meat was the cause of this decline or if other key variables that played a key role. These additional variables will include hay prices, corn prices, oat price, gas prices, and a macro economic indicator variable. The regression results show that the horse slaughter ban did in fact have an impact on the decline of the total number of thoroughbreds sold within this specific segment of the industry. Also, both hay and the unemployment rate had an effect on the decline of the total number of thoroughbreds sold, while gas prices appear to have had an unexpected positive effect, which is contrary to common thought. This thesis shed a new light on the decline of the horse industry within the United States and the effect the ban has had on the thoroughbred industry.
Keywords: Horse Slaughter Ban; Thoroughbred; Economics (0501); Economics, Agricultural (0503)